SIFO 1989: Speed limits and inner-city tolls - Bilriksdagen; Swedish Institute of Public Opinion Research (Swedish Institute of Public Opinion Research, 1993)
This survey includes questions on speed limits on different types of roads, reason why it would be good/bad to lower the speed limit, attitude to the way authorities look after the obedience of speed limits, and actions for getting more drivers to follow the speed limits. Opinion on limiting motorism in central parts of big cities and introduction of different types of inner-city tolls. Background variables include information on gender, place of living, age, Swedish citizenship, occupation, private or public sector, trade union, entitled to vote, political party preference and party voted for in 1988.

Denna undersökning omfattar frågor om hastighetsbegränsningar på olika typer av vägar, orsaker till varför det är bra/dåligt att sänka hastighetsbegränsningen, åsikter om hur myndigheter ser till att hastighetsbegränsningarna åtföljs och de åtgärder som görs för att få fler bilförare att följa hastighetsbegränsningen. Åsikter om begränsning av bilism i centrala delar av storstäder och införandet av olika typer av avgifter i städers centrala delar. Bakgrundsvariabler inkluderar information om kön, ort, ålder, svenskt medborgarskap, yrke, privat eller offentliga sektor, fackföreningsmedlemskap, politiska preferenser och vilket parti som de röstat för 1988.
SIFO 1989: Hastighetsgränser och bilavgifter
Keywords: TRANSPORT AND TRAVEL; TRANSPORT OCH RESOR; Social Sciences; Samhällsvetenskap